Identification and Characterization of T5-Like Bacteriophages Representing Two Novel Subgroups from Food Products - Sváb, Domonkos; Falgenhauer, Linda; Rohde, Manfred; Szabó, Judit; Chakraborty, Trinad; Tóth, István (Frontiers in Microbiology, 2018)
During recent years, interest in the use of bacteriophages as biocontrol agents against foodborne pathogens has increased, particularly for members of the family Enterobacteriaceae, with pathogenic Escherichia coli, Shigella and Salmonella strains among them. Here, we report the isolation and characterisation of 12 novel T5-like bacteriophages from confiscated food samples. All bacterophages effectively lysed E. coli K-12 strains with an average burst size of 40 PFU/cell and were able to infect pathogenic E. coli strains representing enterohaemorrhagic (EHEC), enteropathogenic (EPEC), enterotoxigenic (ETEC) and enteroinvasive (EIEC) pathotypes, Shigella dysenteriae, S. sonnei strains, as well as multidrug-resistant (MDR) E. coli and multiple strains representing different Salmonella enterica serovars. All the bacteriophages exhibited Siphoviridae morphology. Whole genome sequencing of the novel T5-like bacteriophages showed that they represent two distinct groups, with the genome-based grouping correlating to the different host spectra. As these bacteriophages are of food origin, their stability and lack of any virulence genes, as well as their broad and mutually complementary host spectrum makes these new T5-like bacteriophages valuable candidates for use as biocontrol agents against food-borne pathogenic enterobacteria.